I-PASS Handoff Curriculum: Campaign Toolkit - Glenn Rosenbluth; Shilpa J. Patel; Lauren A. Destino; Jennifer L. Everhart; Jennifer K. O'Toole; Adam T. Stevenson; Clifton E. Yu; Sharon Calaman; April D. Allen; Amy J. Starmer; Nancy Dollase Spector; Christopher P. Landrigan; et al. (Association of American Medical Colleges, 2013)
Abstract The suite of I-PASS Campaign materials is designed to ensure successful I-PASS implementation at your institution. An Implementation Workbook and Curriculum Log are provided that give practical step-by-step instructions regarding I-PASS planning, development, and implementation. The Just in Time Didactic is a condensed presentation that revisits the major components of the I-PASS curriculum, and is designed for team members who may not have been using I-PASS recently (e.g., clinicians who may have substantial non-clinical commitments) as well as those who want a quick refresher. Speaker notes are provided to assist presenters. The visual advertising campaign includes standard-size pocket reference cards, screen frames for computer monitors, and posters for work areas, all of which can be produced locally using templates included within this Toolkit. I-PASS Tips of the Day could be formatted for printing as flip-books to display on chart racks or nursing stations, and mini-Tips can be tucked into fortune cookies! To ensure that you stay organized throughout the process, refer to the Implementation Workbook to keep track of key elements and timelines. Together and individually, these campaign materials will be essential for your successful I-PASS implementation. In brief, we found in a detailed review of 10,740 patient admissions that a 23% reduction in medical errors and a 30% reduction in injuries due to medical errors (preventable adverse events) occurred following implementation of the I-PASS Handoff Bundle in nine academic medical centers. In direct observation of thousands of hours of resident workflow (time motion analysis) before and after implementation of the program, conducting handoffs using the I-PASS method was found to require no more time per handoff, and resident workflow throughout the shift was likewise unchanged, including no change in the amount of time spent at the computer or in direct patient care.